Co-design and footwear: Breaking boundaries with online customization interfaces - Oliveira, Nelson (2019)
In the current era of valuing and sharing experiences, the consumer states being proudly eager to actively intervene in the construction of his/her own sphere of action. Having humanitarian and socializing dimensions in its essence, the practice of design reveals itself capable of breaking barriers and broadening physical and conceptual horizons, to fulfil its main purpose—the satisfaction of consumers’ needs and desires. Co-design, as a win-win shared experience for brands and consumers, responds to the commercial needs of brands and to the consumers’ needs of interaction, customization, and emotional involvement. This approach between stakeholders is strongly enhanced by new technologies and digital environments, blurring boundaries between designer and consumer/user and overcoming physical constraints. In the footwear sector, some brands recognize the potential of this method, focusing on the development of online customization platforms. Thus, using the content analysis method, based on the study of three of these user interfaces, it is intended to present a proposal of a model for a platform-user relational analysis able to assist the development of online footwear customization interfaces. It is aimed to contribute to the theoretical reflection of the co-design applied to the customization of footwear.